2017
DOI: 10.3386/w23260
|View full text |Cite
|
Sign up to set email alerts
|

Pass-Through as a Test for Market Power: An Application to Solar Subsidies

Abstract: We formalize pass-through over-shifting as a simple yet under-utilized test for market power. We apply this test in the market for solar energy. Specifically, we estimate the pass-through of solar subsidies to solar system prices using rich micro-level transaction and subsidy data from California. Buyers of solar systems capture nearly the full subsidy, while there is more-thancomplete pass-through to lessees. We conclude that solar markets are imperfectly competitive by ruling out alternative explanations for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…However, CSI records the date when a rebate application is electronically submitted, at which point a signed contract is required by program rules. The application might be submitted by either the homeowner or the contractor, but the subsidy is mainly captured by the homeowner (Pless and van Benthem, 2017). Because a rebate is reserved for the homeowner at the current rate upon submission, the homeowner has the incentive to submit as soon as possible.…”
Section: The California Solar Initiative (Csi)mentioning
confidence: 99%
“…However, CSI records the date when a rebate application is electronically submitted, at which point a signed contract is required by program rules. The application might be submitted by either the homeowner or the contractor, but the subsidy is mainly captured by the homeowner (Pless and van Benthem, 2017). Because a rebate is reserved for the homeowner at the current rate upon submission, the homeowner has the incentive to submit as soon as possible.…”
Section: The California Solar Initiative (Csi)mentioning
confidence: 99%
“…More generally, demand elasticity and demand convexity are (potentially location-specific) determinants of the pass-through (Weyl and Fabinger, 2013). Pless and van Benthem (2019) argue that under specific conditions, a passthrough rate above unity suggests the existence of market power.…”
Section: Theory and Empirical Literaturementioning
confidence: 97%
“…There is likely imperfect competition at higher levels of the distribution chain and in retail markets in remote rural areas, and consumers of public health products are known to be sensitive to price. Third, empirical studies measuring pass-through in a variety of industries have found a range of pass-through rates, including pass-through exceeding 100% in some instances (Pless & van Benthem, 2019).…”
Section: Approaches For Measuring the Equity Of Private Sector Subsidiesmentioning
confidence: 99%